Association of TGF-β3 and ANXA11 with pulmonary sarcoidosis in Greek population - Sikorova, Katerina; Kishore, Amit; Rapti, Angeliki; Adam, Kalliopi; Kocourkova, Lenka; Zizkova, Veronika; Charikiopoulou, Maria; Kalianos, Anastasios; Bouros, Evangelos; Bouros, Demosthenes; Petrek, Martin (Expert review of respiratory medicine, 2020)
BACKGROUND: In sarcoidosis, the direction and intensity of immunological reactions involved in disease pathophysiology is affected by variation in the genes coding for effector and regulatory molecules with immune functions. This study, therefore, investigates polymorphic variants in genes involved in inflammation, immune reactions, and granuloma formation in context of their plausible association with sarcoidosis, with specific focus on Greek population. METHODS: A total of 18 single-nucleotide polymorphisms (SNPs) were genotyped in Greek patients with pulmonary sarcoidosis (n = 103) and in healthy Greek control subjects (n = 100) using multiplexed MassARRAY (MassARRAY ®) iPLEX assay based on MALDI-TOF mass spectrometry. RESULTS: TGF-β3 rs3917200*G variant was associated with sarcoidosis (OR: 3.04 [95% CI: 1.98-4.69], p = 2.76*10-7). Further, ANXA11 rs1049550*A variant was associated with sarcoidosis (OR: 0.59 [0.39-0.89], p = 0.01). CONCLUSIONS: This first study of genetic variation of immune-related genes in Greek patients with sarcoidosis brings to attention a novel disease 'susceptibility' factor: TGF-β3 rs3917200*G allele. It also confirms previously reported 'protective' association between sarcoidosis and functional variant ANXA11 rs1049550*A. Further work is required to validate these findings and to expand investigation of their plausible relationship with clinical course of the disease.
Keywords: genetická predispozice k nemoci; lidé středního věku; annexiny; Genetic Predisposition to Disease; Greek; Male; dospělí; alely; transformující růstový faktor beta3; genotypizační techniky; ANXA11; lidé; senioři nad 80 let; senioři; Aged; Greece; plicní sarkoidóza; běloši; TGF-β3; ženské pohlaví; sarcoidosis; genetic factors; Polymorphism, Single Nucleotide; Aged, 80 and over; Annexins; jednonukleotidový polymorfismus; Adult; Alleles; mužské pohlaví; White People; Sarcoidosis, Pulmonary; Řecko; Transforming Growth Factor beta3; polymorphisms; Middle Aged; Humans; Genotyping Techniques; Female